Digital Land Reform: The Impact of Indonesia’s Electronic Land Administration System on Agrarian Governance - Nazaruddin Halim, Anriz (Journal Evidence Of Law, 2025)
Digital transformation in land administration has become one of the Indonesian government's strategic agendas in order to achieve more modern and accountable land governance. By implementing the Electronic Land Administration System (e-land system), the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) is striving to overcome classic problems in the land sector such as slow bureaucracy, overlapping certificates, land mafia practices, and weak legal certainty. This research employs a qualitative approach with policy analysis methods, utilizing secondary data such as regulations, official reports, academic literature, and media publications. The analysis results show that land digitalization has several positive impacts, including increased transparency, efficiency, accountability, and legal certainty in land management. Programs like PTSL, e-certificates, HT-el, and Roya-el accelerate services, reduce the potential for data manipulation, and strengthen the legal legitimacy of land rights. Nevertheless, the implementation of this policy still faces various challenges, ranging from the digital divide, limitations in technological infrastructure, human resource capacity, to data security issues. Thus, the success of digital agrarian reform depends not only on technology but also on efforts to ensure inclusiveness, strengthen digital literacy, and protect data. The e-land system has great potential to be an effective instrument for agrarian reform, as long as it is implemented evenly and fairly for all Indonesian people.